Cardiogenic Necrotizing Enterocolitis: A Clinically Distinct Entity from Classical Necrotizing Enterocolitis - Siano, Elisa; Lauriti, Giuseppe; Ceccanti, Silvia; Zani, Augusto (European Journal of Pediatric Surgery, 2019)
Aim The main purpose of this study was to investigate if necrotizing enterocolitis (NEC) has a different presentation and outcome in patients with congenital heart defect (CHD) (cardiogenic NEC) from those without (classical NEC).Materials and Methods A systematic review of the literature on the characteristics of infants with NEC and CHD was performed by three independent investigators using a defined strategy (PubMed, Cochrane, Embase, and Web of Science). A meta-analysis was conducted on studies comparing NEC in infants with CHD and non-CHD infants using RevMan 5.3.Results Systematic review: Of 7,291 abstracts screened, 126 full-text articles were analyzed and 51 studies were included. NEC had an incidence of 5.1% in CHD infants (7,728/151,046, range 0–24%) and 0.8% in non-CHD infants (26,430/3,256,891, range 0.1–8.9%; p < 0.0001). In very low birth weight infants, NEC occurred in 6.3% of CHD patients (6,361/100,454pts) and in 8.9% of non-CHD (23,201/257,794pts; p < 0.0001). In CHD cases, NEC occurred before cardiac surgery in 48% cases and surgery for NEC was required in 31% infants (2,037/6,683). Meta-analysis: In eight comparative studies, the incidence of NEC was higher in CHD infants (6%, 768/13,145) than in infants with no CHD (0.9%, 32,625/3,354,323pts; p < 0.00001, odds ratio [OR] 1.84, 95% confidence interval [CI] 1.7–1.9). The overall mortality was higher in infants with CHD and NEC (38%, 243/640) than in those without CHD (27%, 6651/24810; p < 0.00001, OR 3.4, 95% CI 2.8–4.1).Conclusion This is the first evidence-based study showing that infants with cardiogenic NEC have different demographics and outcomes than those with classical NEC. The risk of developing NEC and the mortality rate are higher among infants with CHD than in those without. Conversely, the need for intestinal surgery is lower in babies with cardiogenic NEC than in those with classical NEC. Further studies are needed to establish preventative and management interventions that are specific to infants with or at risk of developing cardiogenic NEC.
Keywords: necrotizing enterocolitis; meta-analysis; systematic review; congenital heart defect; neonates